Cryptococcemia in pancreas-kidney transplant patient - Anass Qasem; Syed Arman Rabbani; Safaa AlKhiami (Medical Mycology Case Reports, 2023)
Solid organ transplant recipients have a higher risk of developing invasive fungal infections (IFIs) due to immunosuppressive therapy. Cryptococcosis is the third most commonly occurring invasive fungal infection in solid organ transplant (SOT) recipients. Cryptococcemia is associated with high mortality rate.We present a case of cryptococcemia in a 31-year-old female with a pancreas-kidney transplant who was admitted to hospital for the management of a suspected Hemodialysis catheter-related bloodstream infection (CRBSI).